Duodenal Obstruction during Pregnancy - Mansooreh Haghiri; Sedigheh Borna; Kamran Hessami; Ali Sharifi; Seyed Mohsen Ahmadi Tafti; Mahrooz Malek; Nasim Pourdamghan; Sedigheh Hantoushzadeh; Abolfazl Shirdel Abdolmaleki; Maasoumeh Saleh (Case Reports in Obstetrics and Gynecology)
Intractable vomiting and elevated liver enzymes during pregnancy seem to be associated to the obstetric etiologies; however, other causes such as acute surgical emergencies should be considered. The patient was a 26-year-old woman at 18 weeks of gestation with intractable vomiting, intolerability of oral intake, weight loss, and absence of abdominal pain. Her physical examinations and laboratory tests had no remarkable findings except elevated liver function test (LFT) and hypokalemia. Considering the lab data and normal abdominopelvic ultrasound, magnetic resonance imaging was performed which revealed dilation of the D1-3 and collapse the D4 sections of duodenum. She underwent exploratory laparotomy which confirmed duodenal obstruction caused by Ladd’s band. After the Ladd’s operation, the patient started oral intake of nutritious, and her LFT decreased to normal ranges. After the last follow-up, she has had gained 18 kg and gave birth at 36 weeks of gestation due to the premature rapture of membranes and delivered a 2 kg small for gestational age otherwise healthy infant. The experience gained from this case was to consider all possibilities (such as small bowel obstruction) and evaluate them in a pregnant patient to consider other causes of nausea, vomiting, and abnormal LFTs in a pregnant patient.